The Information Content Simultaneity of Returns and Earnings: The Case of Indonesia - Fuad Fuad; Dwi Ratmono; Yuserrie Zainuddin (Jurnal Akuntansi dan Bisnis, 2008)
This paper analyzes in detail the information content of returns and earnings, both linearly and simultaneously because they are jointly affected by information that is difficult to specify explicitly. Based on empirical evidence, we challenge the assumption that earnings follow first order moving average process, while assuming that they actually follow first order autoregressive process. Using 900 firm-specific observations from 1996 to 2004 we found that earnings (ERC) and returns response coefficients (RRC) provide similar estimates under joint estimation rather than linear one. We also found that 2-Stage Least Square (2SLS) reduces the bias of ERC and RRC in contrast to under Ordinary Least Square. Surprisingly, earnings and returns convey information larger in the short-term rather than in the long-term. In particular, we found that one year lag of return contain more information about future earning than two-or three years lag of return.